The Relationship Between Fast Food Consumption and the Incidence of Prediabetes in Adolescents at SMA Negeri 1 Limboto - Tri Yuliana Soga; Herlina Jusuf; Sitti Fatimah Meylandri Arsad (Universitas Muhammadiyah Palu, 2025)
Prediabetes is a condition before the occurrence of diabetes mellitus with blood sugar levels above the normal range but not yet meeting the requirements of diabetes mellitus which is a very serious global health problem. Prediabetes has attacked many young adults, adolescents to young children. This study aims to determine the relationship between fast food consumption and the incidence of prediabetes in adolescents at SMA Negeri 1 Limboto. The research design used in this study is a quantitative research with a cross sectional approach. The sample in this study was 203 respondents using the probability sampling technique using the Spearman Rank test. The results showed that fast food consumption in adolescents at SMA Negeri 1 Limboto was found in the category of rarely consuming fast food as many as 139 respondents and the incidence of prediabetes in the normal category (not prediabetes) of 184 respondents (90.6%). The results of the bivariate analysis showed that there were 7 respondents who rarely consumed fast food experienced prediabetes and 12 respondents who often consumed fast food experienced prediabetes with the results of the Spearman Rank test showing that there was a relationship between fast food consumption and the incidence of prediabetes in adolescents at SMA Negeri 1 Limboto with p value = 0.002 < 0.05. The advice from this study is that adolescents can maintain a healthy diet and lifestyle in order to prevent prediabetes.